(In-)formal caregivers' and general practitioners' views on hospitalizations of people with dementia - an exploratory qualitative interview study - Nadine Janis Pohontsch; Martin Scherer; Marion Eisele (BMC, 2017)
Abstract Background Dementia is an irreversible chronic disease with wide-ranging effects on patients', caregivers' and families' lives. Hospitalizations are significant events for people with dementia. They tend to have poorer outcomes compared to those without dementia. Most of the previous studies focused on diagnoses leading to hospitalizations using claims data. Further factors (e.g. context factors) for hospitalizations are not reproduced in this data. Therefore, we investigated the factors leading to hospitalization with an explorative, qualitative study design. Methods We interviewed informal caregivers (N = 12), general practitioners (GPs, N = 12) and formal caregivers (N = 5) of 12 persons with dementia using a semi-structured interview guideline. The persons with dementia were sampled using criteria regarding their living situation (home care vs. nursing home care) and gender. The transcripts were analyzed using the method of structuring content analysis. Results Almost none of the hospitalizations, discussed with the (in-)formal caregivers and GPs, seemed to have been preventable or seemed unjustifiable from the interviewees' points of view. We identified several dementia-specific factors promoting hospitalizations (e.g. the neglect of constricted mobility, the declining ability to communicate about symptoms/accidents and the shift of responsibility from person with dementia to informal or formal caregivers) and context-specific factors promoting hospitalizations (e.g. qualification of nursing home personal, the non-availability of the GP and hospitalizations for examinations/treatments also available in ambulatory settings). Hospitalizations were always the result of the interrelation of two factors: illnesses/accidents and context factors. The impact of both seems to be stronger in presence of dementia. Conclusions Points for action in terms of reducing hospitalization rates were: better qualified nurses, a 24-h-GP-emergency service and better compensation for ambulatory monitoring/treatments and house calls. Many hospitalizations of people with dementia cannot be prevented. Therefore, hospital staffs need to be better prepared to handle patients with dementia in order to reduce the negative effects of hospitalizations.